A rare case report of uterine rupture in a case of suspected septic abortion - Kashi, Ashwini; R., Sheela S.; S., Harshitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
There was a progressive rise in the rate of caesarean sections globally from 17.2% to 21.5% from 2017 to 2021. Caesarean sections have an improved feto-maternal outcome but come with a set of challenges. A second-trimester abortion in a previously scarred uterus is one of them. The incidence of uterine rupture is about 3.8–4.3% in a scarred uterus, which is much higher than in an unscarred uterus. Mifepristone 200 mg orally followed by misoprostol 800 mcg vaginally within 24–48 hours has been proven to be an effective method for medical abortion, but its safety in a previously scarred uterus has not been fully established. A 27-year-old P2L2A1 with two previous caesarean sections at 19 weeks of gestation was referred to our tertiary care center with bleeding per vagina following consumption of medical termination of pregnancy (MTP) pills, followed by dilatation and curettage outside. She was pale, and tachycardia was noted. Septic abortion was suspected due to repeated bouts of fever, raised total counts, and starting on higher antibiotics. Due to persistent tachycardia and computed tomography (CT) findings, she was subjected to exploratory laparotomy, and a uterine rupture was confirmed. She underwent an obstetric hysterectomy as a lifesaving procedure. Second-trimester abortions with misoprostol in a previously scarred uterus require a high index of suspicion and close monitoring. Detecting life-threatening complications early in at-risk patients plays a crucial role in uterine preservation. There is scope for research to incorporate methods like Foley’s induction in these cases. The clinical picture of a ruptured uterus can be initially non-specific, delaying the diagnosis. Surgery depends on the extent of the rupture, maternal hemodynamic status, and family completion. It is challenging to rule out uterine rupture when there is a similar presentation as septic abortion, so ultrasound is the first investigation of choice in the diagnosis of uterine rupture, whereas CT abdomen and pelvis are confirmatory.